Added value of combined acromiohumeral distance and critical shoulder angle measurements on conventional radiographs for the prediction of rotator cuff pathology. (2022) - Hamie, Quemars M.; Huber, Florian A.; Grunder, Vincent; Finkenstaedt, Tim; Marcon, Magda; Ulbrich, Erika; Farshad-Amacker, Nadja A.; Guggenberger, Roman
Abstract: Purpose: To investigate the role of acromiohumeral distance (AHD) and critical shoulder angle (CSA) measurements from conventional radiographs (CR) in isolation and combined (prognostic index PIAHD-CSA ) as predictors of full thickness rotator cuff tendon tears (RCT) and critical fatty degeneration (CFD; i.e. as much fat as muscle). Method: In this retrospective study AHD and CSA were measured in 127 CR. MR arthrograms served as reference standard and were screened for RCT and CFD. Statistical analysis for inter-reader agreement, Spearman's rank correlation, linear stepwise regression and logistic regression for AHD and CSA with ROC analyses including PIAHD-CSA were performed. Results: In 90 subjects (17 females, mean age 36.1 ± 14.1) no RCT were found on MR imaging and served as control group. In 37 patients (13 females, mean age 58.7 ± 13.2) ≥ one RCT was found. Inter-reader agreements rated between к = 0.42–0.82 for categorical and 0.91–0.96 for continuous variables. No significant correlation of AHD and CSA with either age or sex was seen (p = 0.28 and p = 0.74, respectively). Case group had significantly smaller mean AHD (8.7 ± 3.2 vs. 10.8 ± 2.2 mm; p < 0.001) and larger mean CSA (36.5 ± 4.5° vs. 33.1 ± 4.0°; p < 0.001). PIAHD-CSA increased diagnostic performance for prediction of RCT and CFD (AUC = 0.78 and 0.71), compared to isolated AHD (0.74 and 0.71) and CSA (0.71 and 0.66). Conclusions: AHD and CSA do not depend on age or sex but differ significantly between healthy and pathologic rotator cuffs. A decreased AHD is most influenced by infraspinatus muscle atrophy and fatty degeneration. Combined PIAHD-CSA increases diagnostic performance for predicting RCT and CFD. Highlights: Acromiohumeral distance (AHD) and critical shoulder angle (CSA) do not depend on age or sex. CSA and AHD are significantly different in healthy and pathologic rotator cuffs. Combining CSA and AHD into one index (PIAHD-CSA ) increases overall diagnostic performance. A high PIAHD-CSA increases the risk of full thickness rotator cuff tear and critical fatty degeneration.